Handbook of Spirituality, Religion, and Mental Health - Rosmarin, David H.; Koenig, Harold G. (Academic Press, 2020)
Spirituality, religion, and mood disorders / Bruno Paz Mosqueiro, Alexandre de Rezende Pinto and Alexander Moreira-Almeida -- Spirituality, religion, and suicide / Ying Chen and Tyler J. VanderWeele -- Spirituality, religion, and anxiety disorders / David H. Rosmarin and Bethany Leidl -- Spirituality/religion and obsessive-compulsive-related disorders / Jonathan S. Abramowitz and Jennifer L. Buchholz -- Spirituality, religion, and psychotic disorders / Philippe Huguelet -- Spirituality, religion, and eating disorders / P. Scott Richards, Sarah Weinberger-Litman, Michael E. Berrett and Randy K. Hardman -- Spirituality/religion and substance use disorders / Hilary S. Connery and Jeff Devido -- Spirituality/religion and behavioral addictions / Joshua Briggs Grubbs and Jennifer Tegan Grant -- Spirituality, religion, and marital/family issues / Annette Mahoney, Daniel D. Flint and James S. McGraw -- Spirituality/religion and pain / Christina Rush, Kaitlyn Vagnini and Amy Wachholtz -- Spirituality/religion and end-of-life care / John Peteet.